Factors Affecting Toeic Achievement of The First Semester Students of Informatics Engeneering - Marginingsih, Marginingsih; Makmun, Syaifudin (Syntax Literate, 2020)
The purpose of this study is to conduct case study on the factors affecting TOEIC pre-test grades of the students of Informatics Engineering in Duta Bangsa University in the academic year of 2019/2020. The respondents are 10 students. The data were obtained by interviewing, questionnaire and collecting the documents from the students TOEIC grades. The data were in the forms of interview transcripts and documents. Then grounded theory was used to analyse the data. The result showed that in terms of internal factors, all of the students have interest in English because they like watching Film from YouTube or cinema with or without subtitle so they motivate to learn English. While from the external factors in terms of family background, six students come from educated family. They encourage their children in learning process. While, four students have parents who works as entrepreneur. They learn English by themselves not because their parents ask them to do. Two students said they won English competition at school. One student said the school really improve his English lesson. Three students have their own community at school. They can sometimes share, chat and talk in English. While the rest of students did not mention explicitly if school give impact on their English. Keywords: Internal factors; external factors; improve